Biofortified indica rice attains iron and zinc nutrition dietary targets in the field - Trijatmiko, Kurniawan R; Dueñas, Conrado; Tsakirpaloglou, Nikolaos; Torrizo, Lina; Mae Arines, Felichi; Adeva, Cheryl; Balindong, Jeanette; Oliva, Norman; Sapasap, Maria V; Borrero Correa, Jaime C.; Rey, Jessica; Francisco, Perigio; et al. (Springer, 2016)
More than two billion people are micronutrient deficient. Polished grains of popular rice varieties have concentration of approximately 2 μg g−1 iron (Fe) and 16 μg g−1 zinc (Zn). The HarvestPlus breeding programs for biofortified rice target 13 μg g−1 Fe and 28 μg g−1 Zn to reach approximately 30% of the estimated average requirement (EAR). Reports on engineering Fe content in rice have shown an increase up to 18 μg g−1 in glasshouse settings; in contrast, under field conditions, 4 μg g−1 was the highest reported concentration. Here, we report on selected transgenic events, field evaluated in two countries, showing 15 μg g−1 Fe and 45.7 μg g−1 Zn in polished grain. Rigorous selection was applied to 1,689 IR64 transgenic events for insert cleanliness and, trait and agronomic performances. Event NASFer-274 containing rice nicotianamine synthase (OsNAS2) and soybean ferritin (SferH-1) genes showed a single locus insertion without a yield penalty or altered grain quality. Endosperm Fe and Zn enrichment was visualized by X-ray fluorescence imaging. The Caco-2 cell assay indicated that Fe is bioavailable. No harmful heavy metals were detected in the grain. The trait remained stable in different genotype backgrounds.